Easy to Harm, Hard to Heal: Patient Views About the Back. Issue 11 (1st June 2015) - Darlow, Ben; Dean, Sarah; Perry, Meredith; Mathieson, Fiona; Baxter, G. David; Dowell, Anthony
Abstract : Study Design: Qualitative interview study. Objective: Explore attitudes, beliefs, and perceptions related to low back pain (LBP) and analyze how these might influence the perceived threat associated with back pain. Summary of Background Data: Psychological factors that contribute to the perceived threat associated with LBP play an important role in back pain development and the progression to persistent pain and disability. Improved understanding of underlying beliefs may assist clinicians to investigate and assess these factors. Methods: Semistructured qualitative interviews were conducted with 12 participants with acute LBP (<6-wk duration) and 11 participants with chronic LBP (>3 mo duration). Data were analyzed thematically using the framework of Interpretive Description. Results: The back was viewed as being vulnerable to injury due to its design, the way in which it is used, and personal physical traits or previous injury. Consequently, participants considered that they needed to protect their back by resting, being careful with or avoiding dangerous activities, and strengthening muscles or controlling posture. Participants considered LBP to be special in its nature and impact, and they thought it difficult to understand without personal experience. The prognosis of LBP was considered uncertain by those with acute pain and poor by those with chronic pain. These beliefs combined to create a negative (mis)representation of the back. Conclusion: Negative assumptions about the back made by those with LBP may affect information processing during an episode of pain. This may result in attentional bias toward information indicating that the spine is vulnerable, an injury is serious, or the outcome will be poor. Approaching consultations with this understanding may assist clinicians to have a positive influence on beliefs. Level of Evidence: 3 Abstract : Supplemental Digital Content is Available in the Text.Qualitative interviews were conducted with people experiencing acute and chronic low back pain. Beliefs that the back was vulnerable and needed protection, that back pain was special, and that the prognosis was uncertain or poor created a negative view of the back and increased perceived threat associated with back pain.